Voyagers and Voyeurs: Supporting Asynchronous Collaborative Visualization. - Heer, Jeffrey; Viégas, Fernanda B.; Wattenberg, Martin (Communications of the ACM, 2009)
This article describes mechanisms for asynchronous collaboration in the context of information visualization, recasting visualizations as not just analytic tools, but social spaces. We contribute the design and implementation of sense.us, a Web site supporting asynchronous collaboration across a variety of visualization types. The site supports view sharing, discussion, graphical annotation, and social navigation and includes novel interaction elements. We report the results of user studies of the system, observing emergent patterns of social data analysis, including cycles of observation and hypothesis, and the complementary roles of social navigation and data-driven exploration.